2013
DOI: 10.1055/s-0033-1343615
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Templating with Patient-Specific Instrumentation in Total Knee Arthroplasty

Abstract: Magnetic resonance imaging (MRI) or computed tomography-based patient-specific instrumentation (PSI) may allow for reliable alignment and fewer outliers when compared with conventionally instrumented total knee arthroplasty (TKA). However, some authors have suggested that frequent intraoperative surgeon-directed changes may still be required. This study evaluated the accuracy of PSI to predict component sizing and alignment during TKA. A total of 84 patients (89 knees) who underwent a TKA using a PSI system we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 31 publications
1
39
1
Order By: Relevance
“…Issa et al . reported 29 intraoperative changes in 89 primary TKAs using PSI technology. The above factors may account for the discrepancy between the theoretical advantages and the reality.…”
Section: Discussionmentioning
confidence: 99%
“…Issa et al . reported 29 intraoperative changes in 89 primary TKAs using PSI technology. The above factors may account for the discrepancy between the theoretical advantages and the reality.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, another Level II study demonstrated that cuts achieved with PSI did not correspond to the preoperative plan when checked intraoperatively with computer-assisted navigation tools [10]. Only a single Level II study concluded that minimal changes were required to the preoperative plan laid out by the PSI manufacturer [15]. The consensus of the two studies that addressed this question was that the use of patient-specific cutting blocks did not confer any functional gains when compared with traditional instrumentation.…”
Section: Domentioning
confidence: 99%
“…Total knee arthroplasty [11][12][13][14][15][16][17][18] , total hip arthroplasty [19][20][21] , hip resurfacing 22 , pelvic and acetabular procedures [23][24][25] , and spinal deformities 26,27 have all utilized patient-specific instrument technology with varying degrees of success. Recently, patientspecific instrumentation was found to improve glenoid component placement in both the version and inclination planes when compared with standard two-dimensional surgical planning 28,29 .…”
mentioning
confidence: 99%